A Prospective Study of Vitamin D Supplement in Thyroidectomy Patients Based on Relative Decline of Parathyroid Hormone - Hao, Qing; Qin, Yun; Zhao, Wanjun; Zhang, Lingyun; Luo, Han (Frontiers in Pharmacology, 2021)
Background: In post-thyroidectomy patients, hypocalcemia is the most common complication to prolong hospital stay and decrease patients’ satisfaction. Based on current evidence, it is recommended to supply vitamin D to patients with high risk of developing hypocalcemia. However, how to stratify the risk of patients remains challenging. Aim: We conducted a prospective study to evaluate the effect of vitamin D supplement (calcitriol) on high-risk hypocalcemia patients based on relative decline of parathyroid hormone (RDP). Methods: RDP was calculated by difference between preoperative and postoperative first day PTH divided by preoperative PTH. Patients who underwent total thyroidectomy in addition to bilateral central compartment dissection were enrolled prospectively and were divided into two cohorts. Cohort I: patients with RDP ≤70% and Cohort II: patients with RDP >70%. Patients in Cohort I were then randomly assigned to Group A or B, and patients in Cohort II were randomly assigned to Group C or D. All Groups received oral calcium, and patients in Groups B and D also received calcitriol. All patients were followed for one year. In the study, standard procedure dictates that only oral calcium is given to patients whose RDP ≤70% and that oral calcium and calcitriol is given to patients whose RDP >70%. Therefore, Cohort I Group A and Cohort II Group D are controls in this study. Results: The incidence of clinical hypocalcemia in Groups A and D (the controls) was 11.0% (10/91), and 17.6% (16/91) required additional intravenous calcium. Of note, no patients developed permanent hypocalcemia. Furthermore, calcitriol supplement did not have significant impact on clinical outcomes between Group A and B in Cohort I. By contrast, calcitriol supplement significantly improved clinical outcome by comparing Groups C and D (Cohort II), as marked by clinical hypocalcemia, need of requiring intravenous calcium and long-termed decreased levels of PTH. Conclusion: Supplying calcitriol based on RDP cutoff of 70% may be a wise practice in thyroidectomy patients, and RDP 70% may be a useful predictor to stratify high-risk patients.